19 Childhood cancer health outcomes in egypt: ten-year real-world evidence from children's cancer hospital 57357 – egypt (CCHE) and comparison with results from england. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Soliman, Ranin; Elhaddad, Alaa; Oke, Jason; Eweida, Wael; Sidhom, Iman; Mahmoud, Sonia; Abdelrahman, Hany; Moussa, Emad; Sedki, Mohamed; Zamzam, Manal; Zekri, Wael; Hafez, Hanafy; et al.
Abstract : Objectives: To study childhood cancer survival and health outcomes over the last ten years in one Egyptian hospital CCHE (Children's cancer Hospital 57357 Egypt); determine the variations in survival by demographic, cancer type, and disease severity differences and the reasons behind these variations; and compare childhood cancer survival outcomes with results from England. Method: A retrospective observational cohort study was conducted for children (age 0-18 years) with confirmed cancer diagnosis who presented at CCHE for treatment from 2007 until 2017 and were followed up until July 2018. Confirmed diagnosis of childhood malignancy followed the WHO/ICCC-3 criteria. Patients' demographic data were extracted from hospital-based cancer registry, while disease-related and health outcomes data were extracted from hospital disease-specific registry. Health outcomes included 5-year survival rates, age-standardized mortality rates, and trends in disease relapse/progression. Five-year overall survival was calculated for each childhood cancer type using Kaplan Meier analysis. The 5-year overall survival rates at CCHE were compared to population-based 5-year survival of children with cancer in England [2001–2015]. Comparable survival was defined as < 10% difference and > 10% as inferior survival. Patients' demographics were described for the full-analysis population, and health outcomes evaluation was done for the evaluable population, based on intention-to-treat analysis. Results: A total of 15, 997 children with cancer were analyzed; 58% were males and 42% females. Most of the patients (48%) were in the youngest age group [0–4 years]. Fifty-nine percent of patients had solid tumors and 41% had hematologic malignancies. The most common cancers were Leukemia, Lymphoma, CNS tumors, and Neuroblastoma. Survival was calculated for 14, 553 patients, representing 92.2% of full study population. 5-year survival rates at CCHE were comparable for some cancer types; 95.6% for Hodgkin's Lymphoma; 81% for Non-Hodgkin's Lymphoma; 92.3% for Retinoblastoma; 82% for Renal tumors; 66.4% for CNS tumors; 65.9% for Ewing Sarcoma; 86.9% for Germ cell tumors; 61% for Rhabdomyosarcoma; 77.1% for other soft tissue tumors; and 91.2% for CML. Whereas for other cancer types, overall survival rates at CCHE were inferior; 79.9% for ALL; 53.8% for AML; 56.5% for Neuroblastoma; 56.4% for Hepatoblastoma; 49.1% for Osteosarcoma. Trends in age-adjusted mortality-rates will presented. Conclusions: Studying 5-year survival in childhood cancer health outcomes at CCHE would help generate real-world evidence about those having inferior outcomes and identify priority areas that need future improvements. Making better use of the evidence generated at CCHE would enhance real-world practice through making informed decisions that are adapted to a local context setting– CCHE.